The impact of COVID‐19 on clinical outcomes among acute myocardial infarction patients undergoing early invasive treatment strategy. Issue 10 (30th August 2022) - Sharma, Prerna; Shah, Kajal; Loomba, Johanna; Patel, Arti; Mallawaarachchi, Indika; Blazek, Olivia; Ratcliffe, Sarah; Breathett, Khadijah; Johnson, Amber E.; Taylor, Angela M.; Salerno, Michael; Ragosta, Michael; et al.
Abstract: Background: The implications of coronavirus disease 2019 (COVID‐19) infection on outcomes after invasive therapeutic strategies among patients presenting with acute myocardial infarction (AMI) are not well studied. Hypothesis: To assess the outcomes of COVID‐19 patients presenting with AMI undergoing an early invasive treatment strategy. Methods: This study was a cross‐sectional, retrospective analysis of the National COVID Cohort Collaborative database including all patients presenting with a recorded diagnosis of AMI (ST‐elevation myocardial infarction (MI) and non‐ST elevation MI). COVID‐19 positive patients with AMI were stratified into one of four groups: (1a) patients who had a coronary angiogram with percutaneous coronary intervention (PCI) within 3 days of their AMI; (1b) PCI within 3 days of AMI with coronary artery bypass graft (CABG) within 30 days; (2a) coronary angiogram without PCI and without CABG within 30 days; and (2b) coronary angiogram with CABG within 30 days. The main outcomes were respiratory failure, cardiogenic shock, prolonged length of stay, rehospitalization, and death. Results: There were 10 506 COVID‐19 positive patients with a diagnosis of AMI. COVID‐19 positive patients with PCI had 8.2 times higher odds of respiratory failure than COVID‐19 negative patients ( p  = .001). The odds of prolonged length of stay were 1.7 times higher in COVID‐19 patients who underwent PCI ( p  = .024) and 1.9 times higher in patients who underwent coronary angiogram followed by CABG ( p  = .001). Conclusion: These data demonstrate that COVID‐19 positive patients with AMI undergoing early invasive coronary angiography had worse outcomes than COVID‐19 negative patients.